2020
DOI: 10.3390/su12208317
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mapping of Soil Salinity and its Impact on Paddy Lands in Jaffna Peninsula, Sri Lanka

Abstract: Soil salinity is a major threat to land productivity, water resources and agriculture in coastal areas and arid and semi-arid regions of the world. This has a significantly negative effect on the land and causes desertification. Monitoring salt accumulation in the soil is crucial for the prevention of land degradation in such environments. This study attempted to estimate and map soil salinity in Jaffna Peninsula, a semi-arid region of Sri Lanka. A Partial Least Squares Regression (PLSR) model was constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The efficiency of different soil salinity indices derived from Sentinel 2 imageries (multispectral 10 m) for detecting and mapping soil salinity for this study area has been reported in an earlier study [7]. The results showed that a partial least squares regression (PLSR) model in combination with salinity indices provided the best results compared to the other models investigated.…”
Section: Soil Salinity Mapping and Validationmentioning
confidence: 71%
See 3 more Smart Citations
“…The efficiency of different soil salinity indices derived from Sentinel 2 imageries (multispectral 10 m) for detecting and mapping soil salinity for this study area has been reported in an earlier study [7]. The results showed that a partial least squares regression (PLSR) model in combination with salinity indices provided the best results compared to the other models investigated.…”
Section: Soil Salinity Mapping and Validationmentioning
confidence: 71%
“…Soil salinity was measured by using electrical conductivity (EC) measurements following the 1:5 soil saturation extract method [24] using an electrical conductivity meter. Refer to Gopalakrishnan and Kumar [7] for more details on soil sampling and salinity determination.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…According to Chivasa et al (2001), the poor stand establishment of tropical crops in semi-arid regions of Zimbabwe is primarily due to low-quality seeds, poor sowing techniques and low soil moisture. Salinity has affected above 800 million hectares of the global area (Gopalakrishnan and Kumar, 2020). The expansion rate of soil salinization indicates that more than 50% of global arable land will be affected by 2050 (Tisarum et al, 2020).…”
Section: Fragile Ecosystemsmentioning
confidence: 99%